Education and Tourism: Optimizing Offline Learning through Snakes and Ladders Game at the Islamic Tourism Study Program of IAIN Parepare - Adhitia Pahlawan Putra; Mustika Syarifuddin; Muhammad Munzir; Muh Asrul; Andi Hasan Basri (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: This article's goal is to suggest classroom action research to enhance tourism learning through the game of snakes and ladders. Method: This study was conducted in a classroom setting from October 18 through November 14, 2021. 33 students are the study's participants. There were four stages of this classroom action research project: planned, stages, preparation, execution, and assessment. Result: The class activity revealed that no students in the first cycle received a pre-test score of 75, that only 5% of students actively engaged in their learning, and that the classroom environment was monotonous. Contrary to the previous cycle, cycle II's use of the snake and ladder game resulted in a score of 98 percent for students who scored above the 75th percentile and an increase in participation of 90 percent. Additionally, they participate in their education actively and expressively, which has a favorable impact on the learning environment. Contribution: In various segments, including PAUD, elementary, and junior high schools, snakes and ladders media has long been used to motivate students to learn, improve learning outcomes, and boost self-confidence. However, incorporating tourism into snakes and ladders media with the student segment is novelty and adds contribution to articles about this.